Relationship Between Math Anxiety and Problem-Solving in Dyscalculic Children: Mediating Role of Working Memory - Gilasiyan, Maryam (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: The present study aimed to examine the relationship between math anxiety and problem-solving ability in children with developmental dyscalculia, with a specific focus on the mediating role of working memory. Methods and Materials: This research employed a descriptive correlational design. A sample of 400 students diagnosed with dyscalculia was selected from elementary schools in Tehran using stratified random sampling, based on the Morgan and Krejcie table. Data were collected using three validated instruments: the Mathematics Anxiety Rating Scale for Elementary Students (MARS-E), the Working Memory Rating Scale (WMRS), and the Problem-Solving Inventory for Children. Data analysis was conducted using SPSS-27 for descriptive statistics and Pearson correlation analysis, while Structural Equation Modeling (SEM) was performed using AMOS-21 to test the hypothesized mediational model. Findings: Results revealed that math anxiety was negatively correlated with both working memory (r = –.46, p < .001) and problem-solving ability (r = –.39, p < .001), while working memory had a significant positive correlation with problem-solving (r = .51, p < .001). SEM results indicated a good model fit (χ²/df = 2.06; CFI = 0.96; RMSEA = 0.051). Math anxiety significantly predicted working memory (β = –.46, p < .001), and working memory significantly predicted problem-solving ability (β = .51, p < .001). The direct path from math anxiety to problem-solving was weak but significant (β = –.09, p = .031), while the indirect effect through working memory was stronger (β = –.23, p < .001), confirming partial mediation. Conclusion: The findings demonstrate that working memory plays a significant mediating role in the relationship between math anxiety and problem-solving in dyscalculic children. Educational interventions aimed at enhancing working memory and reducing math anxiety may be effective in improving problem-solving skills in this population.